Konfigurasi Fonem pada Leksikon Peralatan Rumah Tangga Tradisional yang Memiliki Kesamaan Medan Makna - M Suryadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
The aim of this research is to describe the phoneme configuration which is located in the ultima position within the lexicon of traditional household appliances. The phoneme configuration has nuances that mean local wisdom and social intelligence of Javanese ancestors. This type of research is descriptive-qualitative. The research locus is in Pati regency. Data collection methods used were observation and in-depth interviews. The data analysis method used is the distributional method: which is supported by the sorting and comparison techniques. The padan method is used to analyze lexical semantic elements. The findings of the research show that the configuration of the phoneme lexicon of traditional household appliances in the ultima position has a semantic meaning, a philosophical value and a non-arbiteric meaning. The philosophical value is inherent in the configuration of the phoneme lexicon in the ultima position. Non-arbiter forms occur due to messages attached to phoneme configurations in the lexicon.Keywords: Configuration; household appliances; lexicon; phonemes; traditional.IntisariPenelitian ini memiliki tujuan untuk mendeskripsikan konfigurasi fonem posisi ultima pada leksikon peralatan rumah tangga tradisional. Konfigurasi fonem memiliki nuansa arti yang mencerminkan kearifan local dan kecerdasan sosial leluhur Jawa. Jenis penelitian deskriptif-kualitatif. Lokus penelitian di wilayah Kabupaten Pati. Metode pengumpulan data yang digunakan observasi  dan wawancara mendalam. Metode analisis data memanfaatkan metode agih dengan teknik pilah dan teknik banding. Metode padan dimanfaatkan untuk menganalisis unsur semantik leksikal. Hasil temuan penelitian menunjukkan bahwa konfigurasi fonem yang tersusun dalam leksikon peralatan rumah tangga tradisional memiliki tautan arti semedan makna yang bersifat filosofis dan bersifat non-arbiter.  Nilai filosofis melekat konfigurasi urutan fonem leksikon pada posisi ultima. Bentuk nonarbiter terjadi akibat pesan yang melekat pada konfigurasi fonem dalam leksikon.Kata kunci: Fonem;  konfigurasi; leksikon; peralatan rumah tangga; tradisional